International Electron Devices Meeting. Technical Digest
DOI: 10.1109/iedm.1996.553119
|View full text |Cite
|
Sign up to set email alerts
|

Control of electro-chemical etching for uniform 0.1 μm gate formation of HEMT

Abstract: In the gate recess etching of O.1pm gate HEMT process, the anomalous phenomenon caused by electrochemical etching was found. The isolation region implanted with oxygen ion was etched more deeply than the channel region, which caused a non-flat etched surface. This anomaly effects seriously on the device performaince and its uniformity. We suppressed the anomaly by optimizing the condition of the isolation and the pattern of the device. Flat etched surface was achieved and uniform device characteristics was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…Nevertheless, for devices with gate lengths of approximately 130 nm, 145 nm, and 160 nm, the recess etch depth tends to increase as the gate length increases. These results contradict the report that the recess etch rate decreases as the gate line width increases when Ni is exposed to the recess monitor opening [9,10]. On the other hand, when Pt is exposed, there it has been reported that the etch rate increases as the gate length increases [5].…”
Section: Relationship Between Gate Line Width and Etch Depthcontrasting
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, for devices with gate lengths of approximately 130 nm, 145 nm, and 160 nm, the recess etch depth tends to increase as the gate length increases. These results contradict the report that the recess etch rate decreases as the gate line width increases when Ni is exposed to the recess monitor opening [9,10]. On the other hand, when Pt is exposed, there it has been reported that the etch rate increases as the gate length increases [5].…”
Section: Relationship Between Gate Line Width and Etch Depthcontrasting
confidence: 69%
“…In gate recess etching, a chemical reaction by the etching solution and an electrochemical reaction occurs because the ohmic electrode contained in the electrolyte acts as an anode and the gate recess region acts as a cathode due to an electrochemical potential difference [5][6][7]. For example, an electrode reaction between a substrate and deionized water has been reported [8], as well as the occurrence of electrochemically induced etching nonuniformities, depending on the conductivity of the substrate [9,10]. There are also reports that etching behavior differs depending on the surface material of the ohmic electrode and the size of the monitor opening [5,11].…”
Section: Introductionmentioning
confidence: 99%